The Accounting Profession’s Role in Corporate Governance in Frontier Markets: a Research Agenda - Crittenden II, Carl A.; Crittenden, William F. (Organizations and Markets in Emerging Economies, 2014)
Accountants, and especially auditors, play an essential role in financial reporting of public and private firms. Stakeholders of companies in frontier markets rely on financial reports to assist with uncertainty avoidance. Yet, the rules of the game are evolving and not well known. If firms, financial institutions and individuals are to invest and commit resources within frontier nations, there has to be confidence in the accuracy of financial information. The research ideas generated herein fuse early work on corporate governance with more recent research from a variety of emerging market scholars to develop an agenda for accounting and governance research in frontier markets. It is our belief that the accounting profession will have to take a lead role in creating the standards needed to deal with issues unique to frontier nations and to create the transparency necessary to help stakeholders evaluate risk.